2018
DOI: 10.1108/jpmd-07-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the potentials of wine tourism: the way ahead for Limassol

Abstract: Purpose The paper aims to bring together Limassol’s rich wine culture with the contemporary facet of its developing infrastructure and superstructure as a means through which to promote this city as a tourist destination. Additionally, to identify how Limassol can be experienced in relation to the wine culture based on the experience economy model of Pine and Gilmore (1999) Limassol is a seaside city in Cyprus that has developed extensively over the past few years, with a new infrastructure and superstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…More intense interaction, collaboration, and value co-creation among stakeholders of the Wine Routes is decisive in particular for the Old World of Wine (Contò et al, 2014;Lavandoski et al, 2016a;Liasidou, 2018;Metodijeski and Micev, 2018; Thach and Cogan-Marie, 2018)and more in general for the whole wine sector (Wongprawmas and Spadoni, 2018)but is important also for the Wine Routes of other countries. For example, Wine…”
Section: Relationships and Interactions Of Wine Routes With Territorimentioning
confidence: 99%
“…More intense interaction, collaboration, and value co-creation among stakeholders of the Wine Routes is decisive in particular for the Old World of Wine (Contò et al, 2014;Lavandoski et al, 2016a;Liasidou, 2018;Metodijeski and Micev, 2018; Thach and Cogan-Marie, 2018)and more in general for the whole wine sector (Wongprawmas and Spadoni, 2018)but is important also for the Wine Routes of other countries. For example, Wine…”
Section: Relationships and Interactions Of Wine Routes With Territorimentioning
confidence: 99%
“…The four realms of experience (i.e., 4E's) are educational, entertainment, escapist, and esthetic experiences Gilmore, 1998, 2013). In the study of tourism, researchers have demonstrated the importance of different permutations of the 4Es in evoking consumer reactions (Baerenholdt and Haldrup, 2006;Oh et al, 2007;Hosany and Witham, 2009;Lee and Chang, 2012;Sinclair-Maragh, 2016;Liasidou, 2018), online retailing (Jeong et al, 2009), mobile applications -user interface (Mathwick et al, 2001;Hsu et al, 2021), theme parks (Milman and Tasci, 2018), food outlets at shopping malls (Koronaki and Theodoridis, 2020) and malls and its in-house retail offerings (Sadachar, 2014;Sadachar and Fiore, 2018). Mehrabian and Russell's (1974) environmental psychology technique is a popular methodology for assessing and describing environmental experiences, characterizing human perceptions of physical surroundings using three facets of emotions.…”
Section: Visitors' Experiencementioning
confidence: 99%
“…Cultural elements can be the basis for dynamic and creative tourism experiences (Liasidou, 2018; Marshall and De Villiers, 2015; Borowiecki and Castiglione, 2014; Richards, 2010; Volo, 2010). In general, cultural experiences are important part of the experience economy of Pine and Gilmore (1999, 2011) with culture to be a vital component in experiential tourism (Wiltshier and Clarke, 2017; Mottiar et al , 2016; Volo, 2010, 2009).…”
Section: Theoretical Background Of the Researchmentioning
confidence: 99%
“…The websites use tool bars for historical sites and monuments with particular emphasis on the wine routes/villages. Wine culture consists of an important motivation for the travellers; thus, a rich content of online information seems inevitable to attract wine lovers (Liasidou, 2018, Byrd et al , 2016).…”
Section: Research Findings: Cultural Elements Regions and Content Discoursesmentioning
confidence: 99%